POTENTIAL OF CORAL REEF ECOSYSTEMS FOR DEVELOPING MARINE TOURISM ON PASIR PUTIH BEACH, SUKABUMI DISTRICT - Pasaribu, Roberto Patar; Rahman, Abdul; Djari, Anthon A.; Anasri, Anasri; Kurnia, Pipin (Asian Journal of Aquatic Sciences, 2024)
The coral reef ecosystem is one of the main ecosystems in coastal areas. Physically, it has a role as a protector of the coast from currents and waves, and ecologically, it has a role as a habitat for various marine biota for shelter and foraging. Besides that, with their elegance and beauty, coral reefs can become an attraction for marine tourism. This research aims to describe the condition of the coral reef ecosystem and analyze the suitability of coral reef conditions to determine the potential for marine tourism on Pasir Putih Beach, Sukabumi Regency. The method used is direct observation and measurement of parameters needed to determine the potential for marine tourism. Data processing and analysis were performed using CPCe 4.1 software and Microsoft Excel. The observations and data analysis results show that the potential for marine tourism in Pasir Putih Geopark Ciletuh can be considered reasonable according to the tourism suitability index criteria.